2013
DOI: 10.1021/es403105b
|View full text |Cite
|
Sign up to set email alerts
|

Mixing and Reaction Kinetics in Porous Media: An Experimental Pore Scale Quantification

Abstract: We propose a new experimental set up to characterize mixing and reactive transport in porous media with a high spatial resolution at the pore scale. The analogous porous medium consists of a Hele-Shaw cell containing a single layer of cylindrical solid grains built by soft lithography. On the one hand, the measurement of the local, intrapore, conservative concentration field is done using a fluorescent tracer. On the other hand, considering a fast bimolecular reaction A + B → C occurring as A displaces B, we q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
179
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 174 publications
(188 citation statements)
references
References 43 publications
8
179
1
Order By: Relevance
“…They demonstrated the impact of pore structure on reaction and showed that the interfacial contact area between fluids is important in determining the amount of pore-scale mixing and thus the amount of reaction. De Anna et al (2014) presented a 2D pore-scale experiment of fluid-fluid reactive transport in a porous medium consisting of circular grains that were randomly distributed. They compared the results against a model based on imperfect mixing to estimate the concentration profile of the product of an irreversible bimolecular reaction.…”
Section: Introductionmentioning
confidence: 99%
“…They demonstrated the impact of pore structure on reaction and showed that the interfacial contact area between fluids is important in determining the amount of pore-scale mixing and thus the amount of reaction. De Anna et al (2014) presented a 2D pore-scale experiment of fluid-fluid reactive transport in a porous medium consisting of circular grains that were randomly distributed. They compared the results against a model based on imperfect mixing to estimate the concentration profile of the product of an irreversible bimolecular reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Other techniques have been used for imaging porous media flows (de Anna et al 2014;Rose and Britton 2013;Wildenschild and Sheppard 2013). For HS cell dynamics, fluorescence (Bunton et al 2014), shadowgraphy (Almarcha et al 2010b), interferometry (Almarcha et al 2010a, Grosfils et al 2009, and Schlieren techniques have also been of growing interest.…”
Section: Introductionmentioning
confidence: 99%
“…Of particular note are reactive transport processes in which reaction rates are not limited by fundamental molecular interactions, but instead are controlled by mixing processes (primarily diffusion) at interfaces between fluid and/or solid phases containing the various reactants [44][45][46]. These mixing-controlled reactions are often characterized by sharp local gradients and localized reaction zones; example problems include biologically-mediated natural attenuation of dissolved contaminant plumes [47,48], precipitation/dissolution reactions [10,49,50], incomplete mixing effects on reaction rates [51][52][53][54][55][56][57] and biofilm dynamics [11,58]. There have been many representative pore-scale modeling works on transverse mixing-controlled reactive transport [58][59][60][61][62][63][64][65][66].…”
Section: Introductionmentioning
confidence: 99%